ANALISIS EKSPLOITASI ANAK DALAM TRADISI BUDAK NGAMBEK TIMAH BANGKA BELITUNG - Maulina Hendrik; Muhammad Zikry; Ropita Ropita; Tiara Lenita; Verdy Agustiar (Universitas Islam Sultan Agung, 2026)
This study examines child exploitation in the Budak Ngambek Timah tradition in Central Bangka Regency, Bangka Belitung Islands Province. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. The findings reveal multiple forms of child exploitation economic, physical, social, and educational that negatively impact academic achievement, health, and psychological development. The study recommends comprehensive interventions by the government, educational institutions, parents, and the community to protect children’s rights and eliminate these practices for a better future.